Cover. Issue 4 (11th April 2023) - Ulyte, Agne; Mehrotra, Ateev; Huskamp, Haiden A.; Grabowski, David C.; Barnett, Michael L.
Abstract : The proportion of previous specialty care users with a specialist visit. Note the steep drop in visits to psychiatry after admission to the nursing home. This figure shows the monthly proportion of previous users with a specialist visit. See the related article by Ulyte et al., pages 1058–1067